Evaluation of some biochemical changes in the serum of phensedyl addicts of Gaibandha District, Bangladesh (Journal of Bio-Science, 2014)
Context: Abuse of the drug, Phensedyl like any other drug might exert adverse effects on vital organs of th e h u m an body like liver, kidney and heart. Objectives: To determine the effects of Phensedyl intake on the serum biochemical parameters of the addicts in order to access for damages of vital human organs like liver, kidney and heart. Materials and Methods: Study population consisted of 127 male Phensedyl addicts within the ages of 1855 years of defined criteria from Gaibandha district, a Northern part of Bangladesh, during July 2009 to December 2011. Fifty (50) non-drug dependent healthy men of matched age, height, and socioeconomic status were included as controls from the same community. Biochemical parameters analyzed were Serum creatinine, SGOT, SGPT and Lipid profiles (total serum cholesterol (TC), Serum triglyceride (TG), serum high-density lipoprotein (HDL) and low-density lipoprotein (LDL) cholesterol determined by semiautomatic biochemistry analyzer using commercially available kits Results: Abuse of Phensedyl appears not to hamper the normal renal and liver function in most of the addicts even after 8 years of Phensedyl intake irrespective of age except in case of 4 abusers. Serum total cholesterol (TC) remained almost unchanged among the addicts abusing Phensedyl for less than 8 years. But very strikingly, addicts taking Phensedyl for more than 8 years had higher trends in serum cholesterol i.e. more than 200 ml/dl. Of the addicts, 44.36% abusing Phensedyl for less than 8 years had normal triglyceride (TG) values whereas, in 45.66% addicts abusing the drug for more than 8 years had clinically very significantly elevated triglyceride levels, which was also found to be statistically very significant (p value =0.0001), indicating the risk of developing cardiac diseases. Of the total addicts 53.53% had low levels of HDL cholesterol, which is clinically and statistically found to be very significant (p value =0.002). Of the addicts 43% taking the drug for less than 8 years had normal LDL levels but significantly elevated values were recorded in 34% of the abusers who had been taking the drug for more than 8 years. Conclusion: Long time (> 8 years) Phensedyl abusers are at the high risk of developing Brain stroke, Coronary Heart Disease (CHD), Ischemic stroke or transient ischemic attack (TIA) as there is the triad of: Elevated LDL cholesterol, Low HDL cholesterol and elevated Triglyceride. DOI: http://dx.doi.org/10.3329/jbs.v20i0.17656 J. bio-sci. 20: 57-65, 2012